Hubungan Pendidikan dan Pekerjaan Ibu dengan Status Gizi Anak Pra Sekolah - Niska Niska; Ade Devriany; Fitrah Fitrah (Poltekkes Kemenkes Pangkalpinang, 2017)
Preschool children represeent the group which susceptible to eexperience of nutrient problem. Mother education represent the especial capital in compilation eat the family, mothering and child treatment. On of negativity impact which is felt concerned about at outdoord activity is the lack of construction and child conservancy including the problem of accomlishment of children nutrient level. The purpose of this study is to describe and analyze the correlation betwen education level end mother’s work status with nutritional status in preschool children on kinderganten Pembina 2 Air itam. This research method is an observational research with fisher’s exact approach. The sampling technique used total sampling and in the sample obtained as many as 43 children. Measuring mother's level of education and employment status using questionnaire and nutrition status measure by using scales then the measurement results expressed in z score. Data analysis technique using fisher’s exact. The result of univariate analysis is known that the majority of high educated mothers are 39 people (90.7%), the majority of mothers do not work as many as 13 people (46,5%) and children who have good nutrition status is 36 good nutrition status as much as 36 children (83,7%). The result of fisher’s exactanalysis showed that there wis no correlation between mother’s education status with nutritional status of preschool age children with p value (0,523)